Common Law Constitutionalism Through Methodology - Wheatle, Se-shauna (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
This paper makes the case that methodology is a cornerstone of the advance of common law constitutionalism both within jurisdictions and transnationally. Common law methods, including interpretive presumptions and reasoning by unwritten principles, are central to an appreciation of the development of common law constitutionalism. Moreover, methodological practices present a more fruitful basis for lasting common law constitutionalism in several respects. Firstly, methods have the potential to survive legislative winds of change. Path dependence (in the sense that legal decisions and outcomes are shaped by the historical sequence of legal developments) points to the retention of techniques through embedded judicial practice. Secondly, methods also travel well across borders and thereby enable further development of the transnational dimension of common law constitutionalism. Common law methods are capable of adaptation across borders; they are less susceptible to barriers erected by claims of national or constitutional identity. Against this background, I argue that debates about the merits and impact of common law constitutionalism must contain and respond to accounts of the methods engaged in common law constitutionalist reasoning.